The Development of an Integrated E-Module of Scientific Literacy and Video Demonstration Using a Problem-Based Learning Model for High School Students on Acids and Bases - Yani Puspita Yani; Hardeli Hardeli; Budhi Oktavia; Desy Kurniawati (Postgraduate, University of Mataram, 2022)
This study aims to develop e-module teaching materials based on problem-based learning integrated scientific literacy and demonstration videos on acid and base materials that are useful for assisting the learning process of students. This research belongs to Educational Design Research (EDR) with the Plomp development model. The research tools used are interview forms, validity, and practicality questionnaires. The electronic module is verified by six verifiers, Including three lecturers and chemistry teachers. The data shows that problem-based learning e-module teaching materials and equipped with scientific literacy along with demonstration videos are needed. The data were analyzed using the Content Validity Ratio (CVR), the Aikens'V formula, and the percentage of practicality. Analysis of the validity questionnaire data showed an average CVR score of 1 (for content validity) and Aikens' V average score of 0.88 (for construct validity). Analysis of the practicality questionnaire data showed an average score of 90% and 89% (for small group and field test practicalities). The data analysis shows that the e-module has a high level of validity and practicality. Therefore, it can be concluded that the developed electronic module teaching materials based on problem learning integrated scientific literacy and demonstration videos are valid and practical.